IMPROVEMENT OF REGULATORY AND LEGAL ACTS ON SIMPLIFICATION OF CUSTOMS PROCEDURES BASED ON THE APPLICATION OF THE AUTOMATED RISK MANAGEMENT SYSTEM OF THE CUSTOMS SERVICE OF THE REPUBLIC OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article explains step by step the ways to improve customs administration in the Republic of Uzbekistan, to simplify customs procedures, improve the efficiency of customs authorities, eliminate bureaucratic barriers for entrepreneurship and improve the investment climate in the country. The stages of improvement are considered on the example of one existing normative act and its amendments and additions.